2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626479
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear analysis of autonomic regulation of heart rate variability in healthy first-degree relatives of patients with schizophrenia

Abstract: The recently reported cardiac autonomic dysregulation in patients with schizophrenia is characterized by a decreased vagal and an increased sympathetic modulation. This impairment possibly contributes to the increased cardiovascular mortality rate that is up to three times higher in these patients than in general population. The aim of this study was to characterize the autonomic regulation in schizophrenia and to evidence for a genetic influence. We investigated 36 patients with schizophrenia, 36 healthy firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As a consequence, one could determine whether the possible genetic disposition will lead to an increased incidence of schizophrenia within healthy relatives and whether such a pathological development could be predicted at an earlier stage [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, one could determine whether the possible genetic disposition will lead to an increased incidence of schizophrenia within healthy relatives and whether such a pathological development could be predicted at an earlier stage [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these factors, the dysregulation of the autonomic nervous system (ANS) during acute psychosis has become evident for patients with schizophrenia in studies carrying out heart rate variability (HRV) analysis. Studies applying HRV analyses found reduced vagal and increased sympathetic modulation, indicating a cardiac autonomic dysregulation in patients with schizophrenia and partly in their healthy first-degree relatives [6][7][8][9][10][11][12][13]. The pattern of autonomic dysfunction seen in patients and their relatives might indicate underlying diseaseinherent genetic vulnerability, especially as it was shown by Busjahn et al [14] that a genetic dependency of autonomic parameters (HRV) exists.…”
Section: Introductionmentioning
confidence: 99%
“…HR and SAP time series of patients with acute schizophrenia showed reduced JSDsym, increased JSDdiam and JSDshannon, indicative of impaired baroreflex control [ 77 , 78 ]. Differences in the RR and SAP word distribution matrix were also observed between schizophrenic patients, their first degree relatives and normal subjects [ 79 ]. Similarly, joint symbolic analysis of respiratory interval and RR interval time series showed increased complexity in patients with schizophrenia [ 77 ] and first degree relatives [ 54 ] compared with normal subjects.…”
Section: Joint Symbolic Analysis Of Heart Rate Blood Pressure and Rementioning
confidence: 99%
“…Studies investigating HRV generally showed an altered sympathovagal balance pointing to dysregulation of heart rate for schizophrenic patients and partially their first-degree healthy relatives (Toichi et al, 1999;Valkonen-Korhonen et al, 2003;Bär et al, 2005Bär et al, , 2007Bär et al, , 2010Castro et al, 2009;Chang et al, 2009;Voss et al, 2010). The pattern of an unbalanced ANS (heart rate) in schizophrenic patients and their relatives seem to hallmark a disease-inherent genetic feature of this disease.…”
Section: Introductionmentioning
confidence: 99%